The effect of total debt on net profit in industrial companies - Erwin Indrawan, Hieronimus; Arinie, Astri Julia; Warpindyastuti, Lady Diana; Azizah, Ayu; Al Paksi, Yudha Febri (Institute of Computer Science (IOCS), 2024)
The Company's profit or profit is the main objective of all Companies. Over time and the development of knowledge, the Company's profit or profit is no longer influenced by the amount of sales as income and costs as expenses. The existence of tax levies makes the Company look for various alternatives in financing the company's operational activities. Debt is one of the alternatives that is highly considered by the Company so that the Company's indirect profits can increase and capital can be used effectively and efficiently to obtain profits or profits. This study aims to prove that the rise and fall of debt has an impact on the rise and fall of profits or company profits, the profit or profit referred to is net profit after tax. This study uses quantitative methods with simple linear regression analysis using correlation coefficient tests, determination coefficient tests, and regression equation tests with the aim of determining whether or not there is an effect of Total Debt on Net Profit and significant which is processed using IBM SPSS Statistics software applicationversion 15. The results of the analysis obtained based on the correlation test concluded that between Total Debt showed a significant relationship to Net Profit with a correlation of 0.363 which means weak or low. The results of the determination test show that Total Debt has a significant influence on Net Profit by 13.2% and the remaining 86.8% is influenced by other factors that are not studied. The results of the regression equation formed are Y = 1136652 + 0.252X.